A data‐driven approach for new perspectives on the development of small‐scale H‐Darrieus turbines - Santos, Gabriel Bertacco dos [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Wind energy has emerged as an attractive alternative to the current fossil fuel‐based energy mix. In this context, small‐scale H‐Darrieus vertical‐axis wind turbine (VAWT) combine interesting characteristics for harvesting wind energy in urban‐like conditions. Still, H‐Darrieus turbines are reported to experience relatively low aerodynamic efficiency, especially when compared with horizontal‐axis wind turbines (HAWTs) of equal scale. Even though several devices have been proposed to increase the aerodynamic performance H‐Darrieus turbines, the literature seems to overlook the potential of specifically designed airfoil shapes and blade geometries. In part, this is a direct consequence of the cost of optimization studies for H‐Darrieus turbines. So far, available alternatives rely on limiting either the design exploration or the search algorithm capabilities, which is surely a suboptimal approach for such a complex problem. To overcome the limitations of traditional approaches, we propose here a data‐driven analysis framework that mostly gravitates toward reducing the total computational cost for the optimization of H‐Darrieus turbines. For that, we use computational fluid dynamics (CFD) simulations along with sensitivity analysis, metamodeling, and optimization strategies. Additionally, airfoil shapes are parameterized using a deep generative adversarial network (GAN). The results show that the proposed analysis framework considerably reduces the number of model evaluations required for a complete analysis and optimization. The airfoil parameterization allows expanding the bounds of the latent design space to easily explore novel airfoil designs. The optimized geometries can increase the aerodynamic performance of the turbine by up to 20 % when compared with the NACA 0015 and the NACA 0021—two common airfoil shapes used in H‐Darrieus turbines. Interestingly, the optimized geometries were found outside the original bounds of the design space, further confirming that the search for novel airfoil designs may open the way for better aerodynamic performance of small‐scale H‐Darrieus turbines. To this end, data‐driven strategies may be an interesting approach to indicate new perspective for future development.

A energia eólica emergiu como uma alternativa interessante ao uso de combustíveis fósseis. Neste contexto, as turbinas H‐Darrieus de pequena escala combinam características interessantes para a geração de energia no ambiente urbano. Entretanto, turbinas H‐Darrieus ainda apresentam uma eficiência aerodinâmica relativamente baixa quando comparadas às tradicionais turbinas de eixo horizontal de mesma escala. Diferentes dispositivos foram propostos para aumentar a eficiência das turbinas H‐Darrieus. No entanto, a atual literatura parece ignorar o potencial de geometrias especialmente desenvolvidas para estas turbinas. Em parte, isto ocorre devido ao custo de estudos de otimização em turbinas H‐Darrieus. As atuais alternativas limitam ou a exploração de novas geometrias, ou as capacidades do algoritmo de busca, o que, no fundo, representa uma alternativa subótima para um problema tão complexo. Visando solucionar as deficiências das alternativas tradicionais, propomos aqui uma metodologia de análise baseada em dados, que busca reduzir o custo de estudos de otimização para turbinas H‐Darrieus. Para isto, utilizamos dinâmica dos fluidos computacional combinada com análise de sensibilidade, metamodelagem, e otimização. A geometria dos aerofólios foi parametrizada através de uma rede neural generativa. Os resultados mostram que a metodologia de análise reduz consideravelmente o número necessário de avaliações do modelo numérico para uma análise completa de otimização. O método de parametrização permite expandir os limites do espaço de experimentação para explorar novas geometrias. As geometrias otimizadas podem aumentar o desempenho da turbina em até 20 % em relação ao NACA 0015 e ao NACA0021 — dois modelos normalmente usados em turbinas H‐Darrieus. Interessante o bastante, as geometrias otimizadas foram encontradas fora dos limites originais do espaço de experimentação, indicando que a busca por novas geometrias pode abrir caminhos para o desenvolvimento de turbinas H‐Darrieus mais eficientes. Para isto, estratégias baseadas em dados podem ser uma alternativa interessante para indicar novas perspectivas para desenvolvimentos futuros.
Uma abordagem baseada em dados para novas perspectivas no desenvolvimento de turbinas H-Darrieus de pequena escala
Keywords: Vertical‐axis wind turbine; Computational fluid dynamics; Sensitivity analysis; Aerodynamic optimization; Generative adversarial network; Turbinas de eixo vertical; Dinâmica dos fluidos computacional; Análise de sensibilidade; Otimização aerodinâmica; Rede neural generativa